Variants rs2200733 and rs6843082 Show Different Associations in Asian and Non-Asian Populations With Ischemic Stroke - Wang, Dongsen; Hu, Xuemei; Yang, Xue; Yang, Mingfeng; Wu, Qingjian (Frontiers in Genetics, 2022)
Previous Genome Wide Association Study (GWAS) reported Paired-like homeodomain transcription factor 2 (PITX2) rs2200733 and rs6843082 may one of the risk factors for ischemic stroke (IS) in European population. However, more recently, studies in Asian have reported rs2200733 and rs6843082 are weak or no associated with increased risk of IS. This difference may be due to the sample size and genetic heterogeneity of rs2200733 and rs6843082 among different race. For this study, we searched selected 8 articles with 9 studies from the PubMed and Embase databases , 5 articles from Asian and 3 articles from Non-Asian to evaluated the risk of IS caused by rs2200733 and rs6843082. Then, we investigated the rs2200733 and rs6843082 single nucleotide polymorphisms (SNPs) by analysis using allele, recessive, dominant and additive models. We identified rs2200733 and rs6843082 are weakly significant associated with IS for the allele model (P = 0.8), recessive model (P = 0.8), dominant model (P = 0.49) and the additive model (P = 0.76) in pooled population. Next, we performed a subgroup analysis of the population, the result shown in non-Asian population rs2200733 and rs6843082 have genetic risk for IS, but not in Asian. In conclusion, our analysis shown that the effect of PITX2 rs2200733 and rs6843082 SNPs on IS risk are inconsistent with the effect observed in European IS cohorts.